Food Insecurity and Its Effects on Women's Health: Undernourishment, Physiological needs, HIV/AIDS and NCDs - Md. Ashrafuzzaman; Md. Sayedur Rahman (Budapest International Research in Exact Sciences (BirEx) Journal, 2022)
Food insecurity is threatening populations with its implications on health and nourishment not only in rural but also in urban areas as the poverty patterns shift from developing countries towards rest of the world. Women's presence in agriculture and food production as main labors, their responsibility of caretakers of children which affects future of societies, rising numbers of single mothers in the world and female vulnerability due to physiological needs require particular attention to problems of women caused by food insecurity. This study discusses women's health problems related to food insecurity as health is seen as crucial for survival. This paper analyzed “How does food insecurity affect women's health?” Focus group discussions, interviews, observations, and secondary data were all used in this analysis.